Herpes zoster encephalopathy or acyclovir neurotoxicity: a management dilemma. (28th April 2014) - Sacchetti, Daniel; Alawadhi, Aydah; Albakour, Mustafa; Rapose, Alwyn
Abstract : This is a case report of a 69-year-old morbidly obese woman who presented with mental status changes after she was treated with acyclovir for shingles. The predominant symptoms were word-finding difficulties and visual hallucinations. Complicating her presentation was acyclovir-induced acute renal injury causing her creatinine level to rise up to 7.4 mg/dL. Acyclovir was discontinued on the suspicion of acyclovir neurotoxicity. Even though PCR for varicella zoster virus in the cerebrospinal fluid was positive, acyclovir was not restarted and the patient continued to improve and returned to her baseline.